2022
DOI: 10.9745/ghsp-d-21-00723
|View full text |Cite
|
Sign up to set email alerts
|

“Testing Can Be Done Anywhere”: A Qualitative Assessment of Targeted Community-Based Point-of-Care Early Infant Diagnosis of HIV in Lusaka, Zambia

Abstract: Community-based point-of-care testing is an acceptable, appropriate, and feasible strategy for improving access to HIV diagnostic services for high-risk HIV-exposed infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Due to the unreliable power supply in most rural and semi urban settings, operationalization of PoC platforms would require a sustainable back up such as solar power as a means to ensure continued testing even in the event of power outages. This operational feature is important in resource constrained settings and PoC platforms with the ability to store charge or use a backup power supply have shown to function well even at community levels [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the unreliable power supply in most rural and semi urban settings, operationalization of PoC platforms would require a sustainable back up such as solar power as a means to ensure continued testing even in the event of power outages. This operational feature is important in resource constrained settings and PoC platforms with the ability to store charge or use a backup power supply have shown to function well even at community levels [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given that early infant diagnosis is a crucial metric for assessing the effectiveness of PMTCT programmes, our ndings underscore the need for a strategy to diversify and decentralize laboratories to PMTCT sites and enhance the quali cations of staff conducting these tests. Within the African context, several studies [28][29][30][31][32] re ect this challenge, suggesting that the establishment of an effective PMTCT programme requires investments in deploying and maintaining early infant diagnosis equipment at care facilities, ensuring the availability of essential supplies, and providing training for health care staff. Institutional childbirth among seropositive pregnant women and early infant diagnosis at the national level are generally low, with concerns regarding the regions of Kindia, Kankan, and Boké.…”
Section: Discussionmentioning
confidence: 99%
“…Community POC testing on high-risk mother-infant pairs has also been explored in Zambia, and the results show that it minimizes the structural barriers to EID testing access. However, operational challenges such as client's confidentiality needs to be addressed [34]. We, in Malawi, recently showed that in a busy HIV care clinic, simple strategies (such as tagging of care mastercards), developed by its team using the model of improvement, improved the number of infants receiving their DNA-PCR results (unpublished).…”
Section: Hospitalsmentioning
confidence: 99%